Chiral nitroarenes as enantioselective single-electron-transfer oxidants for carbene-catalyzed radical reactions - Wang, Hongling (2020)
A new class of chiral oxidants is developed. These readily accessible oxidants contain a nitro group for oxidation and a chiral sulfonamide moiety for stereoselectivity control. The chiral information from the oxidants can effectively transfer to the substrates in carbene-catalyzed β-hydroxylation of enals via single-electron-transfer radical processes. We expect these oxidants to find unique applications in other asymmetric oxidations and oxygen-atom-transferring reactions.